Diagnostic Accuracy of MRI In Detection of ACL Tear Keeping Arthroscopy as Gold Standard - Ali, Babar; Qureshi, Adnan Ahmed; Jamali, Abid Hussain; Memon, Ulfat; Shabana (Indus Journal of Bioscience Research, 2025)
Background: Anterior cruciate ligament tear is common knee injury observed in young and active persons mostly. Early and accurate diagnosis is important to prevent instability and long-term complication. Arthroscopy is considered gold standard but it is invasive so imaging methods are needed. Objective: To determine the diagnostic accuracy of magnetic resonance imaging in detection of anterior cruciate ligament tear keeping arthroscopy as gold standard. Study Design: Cross sectional study. Duration and Place of Study: This study was conducted from 7 March 2025 to 7 June 2025 in the Department of Radiology of LUMHS Jamshoro. Methodology: A total of 143 patients aged 15 to 60 years with recent knee injury were included. Magnetic resonance imaging was performed using 1.5 Tesla machine and findings were assessed by radiologist. Arthroscopy was done for confirmation. Data was analyzed using statistical package for social sciences version 22. Diagnostic accuracy parameters were calculated and chi square test was applied. P value ≤0.05 was taken as significant. Results: The mean age was 32.80±7.42 years. Magnetic resonance imaging showed sensitivity of 83.33%, specificity of 92.08%, positive predictive value of 81.40%, negative predictive value of 93.00% and overall diagnostic accuracy of 89.51% (p≤0.05). True positive cases were 35 while true negative was 93. Conclusion: Magnetic resonance imaging is reliable and noninvasive method for detection of anterior cruciate ligament tear with good diagnostic accuracy compared to arthroscopy.